“Without limit of time” living as a restricted patient in Scotland: an interpretative phenomenological analysis - Barnett, Vivienne (Journal of Theoretical and Philosophical Criminology, 2022)
Individuals detained within forensic mental health services in Scotland, under Compulsion and Restriction Orders (COROs), have the greatest theoretical constraints on their liberty of any patients within Scotland’s mental health system. COROs function to aid patients’ recovery but also to prevent harm to the public; unlike civil compulsion where outcomes are measured based solely on recovery. There is a dearth of research exploring patients’ perspectives of compulsory treatment and this study is the first to focus solely on the perspectives of those living under COROs. The current study used Interpretative Phenomenological Analysis to analyse interviews with participants about their experiences of living under restriction. Eleven participants were interviewed: six living in the community under conditional discharge and five residing in low secure care. Four superordinate themes were derived from the data: (1) How did I end up here? (2) Impact: Power, Punishment and Protection (3) Surviving and Adapting (4) Recovery. The results are reviewed in the context of extant findings; clinical implications and areas of future research are considered.